Plan estratégico para el mejoramiento de los servicios de control del tráfico aéreo de la subdirección de aviación civil, en el cantón Guayaquil, provincia del Guayas, periodo 2014 – 2017 - Ruiz Cansiong, Natali Katherine (2015)
This research was developed to elaborate a Strategic Plan to for the improvement of services of air traffic control of the Division of Civil Aviation in Guayaquil, which seeks to improve the service provided by the areas of air traffic control for the period 2014-2017. In order to develop this Strategic Plan was established three fundamental stages which are the formulation, implementation and evaluation of strategy. It then proceeds to detail the most important results that have been obtained from these stages: In this research was elaborated a SWOT analysis which established strengths as organizational structure and variety of services for air traffic control such as authorization controls, ground, tower, approach, route or area and weather conditions was conducted visual / instrumental flight. Regards to the weaknesses was identified as the main problem space or infrastructure for landing aircraft. Among the opportunities can be realized the acquisition of new equipment and hiring more staff while among the threats were detected as problems certain changes in laws or regulations….